La propriété fiduciaire - Frenette, François (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
If we disregard the taxation consequences resulting from the trust, when this institution is considered in its civil law foundation, it may be defined as a means of ownership whereby the owner does not have the right of enjoyment in his or her area of authority. This aspect allows distinguishing trust from substitution. The fact that a trust is a means and not a segmentation of ownership establishes the difference between trust and usufruct.